Mechanisms by which SNX-BAR subfamily controls the fate of SNXs’ cargo - Long, Yaolin; Li, Yang; Xue, Jin; Geng, Wanqing; Ma, Mingxia; Wang, Xiaohui; Wang, Li (Frontiers in Physiology, 2025)
The SNX-BAR subfamily is a component of the sorting nexins (SNXs) superfamily. Distinct from other SNXs, which feature a PX domain for phosphoinositide binding, the SNX-BAR subfamily includes a BAR domain that induces membrane curvature. Members of the SNX-BAR subfamily work together to recognize and select specific cargo, regulate receptor signaling, and manage cargo sorting both with and without the involvement of sorting complexes. They play a crucial role in maintaining cellular homeostasis by directing intracellular cargo to appropriate locations through endo-lysosomal, autophagolysosomal, and ubiquitin-proteasome pathways. This subfamily thus links various protein homeostasis pathways. This review examines the established and hypothesized functions of the SNX-BAR subfamily, its role in intracellular protein sorting and stability, and explores the potential involvement of subfamily dysfunction in the pathophysiology of cardiovascular and neurodegenerative diseases.